REINVENTING KONSEP DIRI DAN MOTIVASI BERPRESTASI DALAM MENCIPTAKAN PRESTASI BELAJAR SISWA - Asiyah Asiyah (Universitas Islam Negeri Fatmawati Sukarno, 2016)
This article is motivated by a phenomenon in the achievement of student achievement that shows that the impulse to achieve the feat of learning in students is still low. Many things that have a positive and significant correlation of student learning achievement associated with them is the concept of self-esteem and achievement motivation of students. View of education experts about increasing and decreasing the learning achievement of individuals can be influenced by the concept of self and motivation of its (Garg, Melanson and Levin, 2007; Marjoribanks, 2003, Hill, Castellino, Lansford, Nowlin, Dodge, and Bates, 2004). The purpose of this paper is to describe the self-concept and achievement motivation and student achievement.